Selective inhibitors of trypanosomal uridylyl transferase RET1 establish druggability of RNA post-transcriptional modifications. Issue 5 (4th May 2017) - Cording, Amy; Gormally, Michael; Bond, Peter J.; Carrington, Mark; Balasubramanian, Shankar; Miska, Eric A.; Thomas, Beth
ABSTRACT: Non-coding RNAs are crucial regulators for a vast array of cellular processes and have been implicated in human disease. These biological processes represent a hitherto untapped resource in our fight against disease. In this work we identify small molecule inhibitors of a non-coding RNA uridylylation pathway. The TUTase family of enzymes is important for modulating non-coding RNA pathways in both human cancer and pathogen systems. We demonstrate that this new class of drug target can be accessed with traditional drug discovery techniques. Using the Trypanosoma brucei TUTase, RET1, we identify TUTase inhibitors and lay the groundwork for the use of this new target class as a therapeutic opportunity for the under-served disease area of African Trypanosomiasis. In a broader sense this work demonstrates the therapeutic potential for targeting RNA post-transcriptional modifications with small molecules in human disease.